A Novel Hydraulic Interconnection Design and Sliding Mode Synchronization Control of Leveling System for Crawler Work Machine - Ruochen Wang; Kaiqiang Zhang; Renkai Ding; Yu Jiang; Yiyong Jiang (Agriculture)
To address the issues of easy overturning and poor safety of crawler work machines operating on steep slopes in hilly and mountainous areas, this study develops a structural design scheme based on a “three-layer frame” structure. An omnidirectional leveling system with hydraulic interconnection is designed to maintain platform stability by ensuring a stationary central point during leveling. Furthermore, a sliding mode synchronization control method based on a disturbance observer is proposed to reduce the synchronization error of the hydraulic cylinders and enhance leveling precision. The system’s performance is validated through an AMESim-MATLAB/Simulink co-simulation platform, demonstrating significant improvements over traditional PID control. Specifically, both lateral and longitudinal leveling times are reduced, rise time decreases by 21.8% on average, and overall leveling time is reduced by 35.5%, with synchronization errors maintained within ±6 × 10−4 m. Finally, physical prototype testing further confirms the system’s effectiveness, achieving an average body inclination error of 2.55% and a hydraulic cylinder synchronization error of 8.2%. These findings validate the feasibility and superiority of the proposed omnidirectional leveling system for the crawler work machine in hilly and mountainous regions.